Consequences of interactions between stormwater infiltration systems, shallow groundwater and underground structures at the neighborhood scale. Issue 8 (14th September 2022) - Pophillat, William; Sage, Jérémie; Rodriguez, Fabrice; Braud, Isabelle
ABSTRACT: This study investigates the interplay between stormwater infiltration devices, shallow groundwater and underground structures (sewer pipes and building foundations) at the neighborhood scale. Considering a hypothetical urban area, different scenarios are designed by varying the underground components taken into account within two soil types. For the least permeable soil, interactions with groundwater reduce the infiltration within devices (−99 to −151 mm/y) and increase the transpiration in surrounding areas (+42 to +50 mm/y). For both soils, the overall water table rise due to infiltration and mounding beneath infiltration devices increases groundwater drainage by sewer pipes and draining systems (+7 to +96 mm/y) and the water elevation differential between opposite walls of impervious structures (up to +1.5 m). In turn, underground structures strongly modify groundwater flow. For the least permeable soil, this directly affects groundwater influence on infiltration and transpiration and thus the overall effects of infiltration strategies at the neighborhood scale.